Management of Anticoagulation in Pregnant Women With Mechanical Heart Valves. Issue 3 (March 2020) - Daughety, Molly M.; Zilberman-Rudenko, Jevgenia; Shatzel, Joseph J.; McCarty, Owen J. T.; Raghunathan, Vikram; DeLoughery, Thomas G.
Abstract : Importance: Mechanical heart valves (MHVs) pose significant thrombogenic risks to pregnant women and their fetuses, yet the choice of anticoagulation in this clinical setting remains unclear. Various therapeutic strategies carry distinct risk profiles that must be considered when making the decision about optimal anticoagulation. Objective: We sought to review existing data and offer recommendations for the anticoagulation of pregnant women with MHVs, as well as management of anticoagulation in the peripartum period. Evidence Acquisition: We performed a literature review of studies examining outcomes in pregnant women receiving systemic anticoagulation for mechanical valves, and also reviewed data on the safety profiles of various anticoagulant strategies in the setting of pregnancy. Results: Warfarin has been shown to increase rates of embryopathy and fetal demise, although it has traditionally been the favored anticoagulant in this setting. Low-molecular-weight heparin, when dosed appropriately with close therapeutic monitoring, has been shown to be safe for both mother and fetus. Conclusions and Relevance: We favor the use of low-molecular-weight heparin with appropriate dosing and monitoring for the anticoagulation of pregnant women with MHVs. Data suggest that this approach minimizes the thrombotic risk associated with the valve while also providing safe and effective anticoagulation that can be easily managed in the peripartum period. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completing this activity, the learner should be better able to: describe the clinical considerations in choosing an anticoagulation strategy for a pregnant patient with an MHV; evaluate the existing data about the safety profile of various anticoagulation strategies and the potential benefits and risks of each approach to the mother and fetus; and discuss one recommended approach to management of mechanical valves in the pregnant patient and assess the clinical nuances associated with each individual patient's decision.